Characterization of the structural, physicochemical, and functional properties of soluble dietary fibers obtained from the peanut shell using different extraction methods - Wang, Lei; Fan, Rui; Yan, Yanhua; Yang, Shuo; Wang, Xuesong; Zheng, Baiqin (Frontiers in Nutrition, 2023)
To propose the possible solution for peanut by-product, peanut shell(PS), this study evaluates the effects of different methods including enzymatic extraction (E-SDF), microwave extraction (M-SDF), and pulsed electric fields extraction (PEF-SDF) on the characterization of soluble dietary fiber (SDF) from peanut shell. We determined the SDF physicochemical properties including water-/oil –holding capacities (WHC, OHC), emulsifying, rheological properties, and the functional properties including pancreatic lipase activity inhibition (PRAI), glucose and cholesterol adsorption capacities (GAC, CAC), as well as the structural properties. The results showed the PEF-SDF possessed the highest WHC, OHC, emulsifying properties. For the structure, the M-SDF and PEF-SDF appeared more complex and porous structures, and they showed the smaller molecular weights. Notably, PEF-SDF showed the strongest capacities in CAC, GAC and PRAI. The results indicate the PEF will be a potential preparation SDF method for a promising dietary fiber source, PS.